2015
DOI: 10.1002/cbdv.201400327
|View full text |Cite
|
Sign up to set email alerts
|

Botanical, Phytochemical, and Anticancer Properties of the Eucalyptus Species

Abstract: The genus Eucalyptus (Myrtaceae) is mainly native to Australia; however, some species are now distributed globally. Eucalyptus has been used in indigenous Australian medicines for the treatment of a range of aliments including colds, flu, fever, muscular aches, sores, internal pains, and inflammation. Eucalyptus oils containing volatile compounds have been widely used in the pharmaceutical and cosmetics industries for a multitude of purposes. In addition, Eucalyptus extracts containing nonvolatile compounds ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…The term Eucalyptus was coined by the French botanist, Charles Louis L'Héritier de Brutelle, in 1788, meaning 'well covered' with reference to the operculate nature of the flower which lacks conspicuous petals and sepals (Rozefelds, 1996;Vuong et al, 2015a). Eucalyptus is mostly indigenous to Australia, with a small number found in the adjacent areas of New Guinea and Indonesia (Gupta et al, 2013;Konoshima & Takasaki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The term Eucalyptus was coined by the French botanist, Charles Louis L'Héritier de Brutelle, in 1788, meaning 'well covered' with reference to the operculate nature of the flower which lacks conspicuous petals and sepals (Rozefelds, 1996;Vuong et al, 2015a). Eucalyptus is mostly indigenous to Australia, with a small number found in the adjacent areas of New Guinea and Indonesia (Gupta et al, 2013;Konoshima & Takasaki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best-known genera in this family is Eucalyptus. This genus covers more than 700 species found in various parts of the world, from which 300 species are extracted essential oils, which are used for their antiseptic and healing properties, fragrance and for food preservation (VUONG et al, 2015). Previous studies performed with essential oils of green leaves of Eucalyptus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves were then transferred to the laboratory and stored at −20 °C to avoid potential degradation of phytochemicals. The leaves were dried at 70 °C for 5 h to constant mass using a dry air oven, then ground to a fine powder using in a commercial grade blender ( Rio ™ Commercial Bar Blender, Hamilton Beach ), sieved (≤ 1 mm) using a 1 mm EFL 2000 stainless steel mesh sieve ( Endecotts Ltd ., London, England) then packed in a sealed container and stored at −20 °C until required.…”
Section: Methodsmentioning
confidence: 99%
“…Eucalypts are one of the worldʼs most important plants, with about twenty eucalypt species being exploited commercially worldwide for their medicinal and pharmaceutical properties as well as for food additives . The classification of the eucalypts, especially recognition of the genus Corymbia has generated considerable controversy . Molecular (nuclear DNA and plastid DNA) and morphological research have indicated that Angophora and Corymbia together are a distinct lineage, separate from Eucalyptus .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation